The Effects of Leadership, Work Safety Culture and Work Safety Climate on Work Motivation Area - Reza Fauzi Jaya Sakti; Didi Hartono; Tri Hananto; Andreas Wahyu Gunawan P; Stefanus M S Sadana (Budapest International Research and Critics University, 2022)
This study partially analyzes the effects of leadership, work safety culture and climate, and work safety climate variables on work motivation are. This study use a quantitative approach and 33 respondents to conduct explanatory research. Multiple linear regression data processing using SPSS for Windows version 21.00. Leadership has a partially significant effect on Work Motivation, as indicated by a p-value of 0.000 (0.05), Safety culture has a positive effect on the realization of work motivation, as indicated by a p-value of 0.538 (>0.05) or there is no significance, and Safety climate has a positive effect on the realization of work motivation, as indicated by a p-value of 0.338 (>0.05) or there is no significance (rejected). On the basis of study results indicating that leadership, safety climate, safety culture, and work motivation are all good, it is intended that the training location would preserve the leadership required by students and enhance work motivation with regard to safety climate and culture. The researchers believe that the results of this study will considerably improve the work motivation of student officers by strengthening their competency at Center for Refresher Education and Improvement of Sailing Science.